Prolonged heat waves reduce the condition index and alter the molecular parameters in the pacific oyster Crassostrea gigas. Issue 133 (February 2023) - De Marco, Antonina; Baldassarro, Vito Antonio; Calzà, Laura; Giardino, Luciana; Dondi, Francesco; Ferrari, Maria Giulia; Bignami, Giorgia; Parma, Luca; Bonaldo, Alessio
Abstract: The entire shellfish farming sector is negatively affected by heat waves. Predictive models show that while heat waves are not predicted to exceed 28 °C in the northern Adriatic Sea over the coming decades, their duration will increase to periods of up to 30 days. Knowledge regarding the effects of heat waves on bivalves at physiological and molecular level is still limited. This study attempted to simulate what will happen in the future in Pacific oysters exposed to prolonged heat waves, assessing morphometric and physiological indices, and investigating the expression level of a number of genes, including the chaperone heat shock proteins HSP70, HSP72 and HSP90, and the factor P53 . A state of stress in the heat wave-exposed animals was found, with loss of body weight and energy resources: despite showing a higher clearance rate, these animals were unable to absorb the nutrients required to maintain homeostasis, as well as demonstrating an alteration in hemolymphatic AST activity, total calcium and magnesium concentration. mRNA levels of all examined genes increased in response to thermal stress, with long-term overexpression, activating cell stress defense mechanisms and modulating the cycle cell. The results of this study indicate that heat waves affect oyster welfare, with consequences for the productivity of the sector due to the lack of salable products. Highlights: Heat waves reduce the pulp yield, but not the algal filtration. Heat waves alter calcium and magnesium hemolymphatic concentrations. Adductor muscle tissue is more sensitive to thermal stress than gills. Thirty days of heat wave cause a decline of heat shock proteins expression in gills.